2016
DOI: 10.1039/c6ra07800a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of calcium phosphate/pectin scaffolds for bone tissue engineering

Abstract: The calcium phosphate cement (CPC) scaffold has been used to repair bone defects, but its low compressive strength and poor osteogenesis greatly hinder its clinical application. Pectin is a natural, biocompatible, biodegradable, water-soluble polysaccharide that can improve the osteogenic activity of biomaterials. In this study, calcium phosphate/pectin cement (CPCP) scaffolds with different pectin concentrations (2%-6%) were prepared. The results showed that changes in the pectin concentration could modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Since no further decrease of cell viability was observed during the incubation, the drop in cell viability after 1 h is likely due to a possible incomplete dissolution of the gel, thus causing an underestimation of the number of cells, as it was possible to observe fragments and deposits after the centrifugation step. The gel environment was able to support cell viability in agreement with the previous research on different pectin gel formulations 15 , 36 , 40 , 41 . Interestingly, the immunological properties of hAMSCs, that is, their inability to induce a T cell response and their ability to inhibit the proliferation of PBMCs activated with anti-CD3, were retained thus indicating that amniotic cells were able to produce the modulatory bioactive molecules even after loading into pectin gel.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since no further decrease of cell viability was observed during the incubation, the drop in cell viability after 1 h is likely due to a possible incomplete dissolution of the gel, thus causing an underestimation of the number of cells, as it was possible to observe fragments and deposits after the centrifugation step. The gel environment was able to support cell viability in agreement with the previous research on different pectin gel formulations 15 , 36 , 40 , 41 . Interestingly, the immunological properties of hAMSCs, that is, their inability to induce a T cell response and their ability to inhibit the proliferation of PBMCs activated with anti-CD3, were retained thus indicating that amniotic cells were able to produce the modulatory bioactive molecules even after loading into pectin gel.…”
Section: Discussionsupporting
confidence: 89%
“…Among pectin gels, CaPs/pectin gels have been previously produced by exploiting the double effect of cross-linker and filler to produce biocomposite gels 38 , 39 or by incorporating nano-hydroxyapatite to support osteoblast growth 40 . The addition of pectin in bone cements, based on CaPs, has been shown to improve the adhesion and proliferation of human adipose tissue-derived stem cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stabilization of these salts into hydrogel matrixes seems to be a promising strategy to overcome such limitation. Zhao et al proposed forming ionic complexes between pectin and calcium phosphate cement to improve the osteogenic activity and mechanical properties of the hydrogel [421]. Changes in the pectin concentration (2-6 w/w.%) allow tailoring the structure and morphology of the scaffold.…”
Section: Pectin-based Hydrogels For Tissue Engineeringmentioning
confidence: 99%
“…Further improvements attributed to the use of pectin were the enhancement of mechanical properties, high cellular attachment, proliferation, and high osteogenetic efficiency. In addition, pre-clinical studies performed in New Zealand on white rabbits using the cavity defect model revealed that the pectin/calcium phosphate cement enables the defect regeneration within 8 weeks [421]. Probably, hydroxyl groups proceeding from pectin would increase the expression of osteogenic genes and matrix mineralization.…”
Section: Pectin-based Hydrogels For Tissue Engineeringmentioning
confidence: 99%
“…1,2 It is protective in heart diseases, hypertension, and diabetes, 3 and it improves the osteogenic activity of biomaterials. 4 Pectin can be obtained from the cell walls of plants such as citrus fruits and apples, and it is byproducts from juice manufacturing units. The molecular weight of pectin and the degree of esterification differs according to pectin source and extraction conditions.…”
Section: Introductionmentioning
confidence: 99%